Design, 3D FEM Simulation and Prototyping of a Permanent Magnet Spherical Motor - Umut Yusuf Gündoğar; Sibel Zorlu Partal (Actuators, 2021)
In recent years, large tilt angles, uniform magnetic flux distributions, strong forces, and large torques for motors have increasingly become important for robotics, biomedical, and automotive applications that have multi-degrees of freedom (MDOFs) motion. Generally, one-degree of-freedom motors are applied in MDOF motion. These situations cause the systems to have very complex and large structures. In order to address these issues, a 2-DOF surface permanent magnet spherical motor with a new mechanical design for the movement of the rotor with a large tilt angle of ±45° was designed, simulated, produced and tested in this paper. The motor consisted of a 4-pole permanent magnet rotor and a 3-block stator with 18 coils. In this study, the mechanical structure of the proposed spherical permanent magnet motor surrounded the rotor with two moving parts to move at a large tilt angle of ±45° without using any mechanical components such as spherical bearings, joint bearings, and bearing covers. Thus, the tilt angle, force, and torque values of the proposed motor have been improved according to MDOF motion motors using spherical bearings, bearing covers, or joint bearings in their mechanical structures in the literature. Ansys Maxwell software was used for the design and simulation of the motor. Three-dimensional (3D) finite element method (FEM) analysis and experimental studies were carried out on the force, torque, and magnetic flux density distribution of the motor. Then, simulation results and experimental results were compared to validate the 3D FEM simulations results.